Correlation between parents' income and students' achievement in Universiti Teknologi Mara Segamat Campus / Ruhana Zainuddin - Zainuddin, Ruhana (2002)
Many research works have been done in other countries to study the association between parents' income and the students' performance in academic. It was found in the study that in younger age, high-income parents are more likely to exert a positive influence in their children's academic achievement. Tests were conducted in schools to study the association, and it was found that low-income population especially with large minority population has students with low tests scores. However not much research has been done in Malaysia regarding this matter. Thereby the researcher decided to conduct this research and the population is targeted at UiTM Segamat Campus students. Do parents' financial background have anything to do with the students' achievement particularly the CGPA is of interest here. A sample of 350 students were obtained and analyzed. The analysis was done by using Pearson Coefficient of correlation . The results are discussed in detail in this study.